Children's Learning Styles in Learning Psychology - Lailatul Badriah; Alimul Muniroh (Magister Programme Of Islamic Education Departement at Institut Agama Islam Tarbiyatut Tholabah, 2025)
Learning Style is a combination of how a person absorbs, organizes, and processes information. Learning styles have existed since childhood and we can change them according to the experience of each student, the purpose of this study is to find out what are the concepts of learning styles, how to identify learning styles, and the application of learning styles in learning. This study uses a qualitative approach with a descriptive-analytical design in the context of children's learning styles. The data collection uses primary and secondary data, observation and interviews, and data analysis is carried out through stages that include data reduction, data presentation, and conclusion drawn. The findings in this study are in the form of the concept of children's learning styles, how to identify learning styles using observation or learning style questionnaires, and the application of learning styles can be seen from several steps that have been presented in the sub-chapters below. The contribution in this study is that it can help identify children's learning styles, especially for teachers, can know the learning style of each child, and with this teachers can design more personalized and effective learning strategies according to the learning style of each child.